Thirty Years of Democratic and Free Elections in Slovakia: Can Really Everyone Vote? Array - Domin, Marek (Acta Universitatis Danubius. Juridica, 2020)
The objective of the paper herein, on the 30th anniversary of the first democratic and free elections after the fall of the totalitarian regime in Slovakia, is to assess whether or not the right to vote in the Slovak Republic really belongs to everyone. The subject of the examination are four categories of persons whom the Constitution of the Slovak Republic and the laws formally grant the right to vote, but in various ways restricted or still resctrict the practical exercise of this right. These groups are as follows: prisoners, intellectually disabled people, persons located abroad and persons who may pose a risk to public health. Not only the valid legal regulation, but also the decision-making activity of the Slovak Constitutional Court, will be the subject of the analysis of the first two categories. The conclusion of the article also includes suggestions and recommendations aimed at ensuring that the right to vote in Slovakia is truly universal, or in other words, recommendations aimed at ensuring an opportunity to vote to everyone whom the Constitution and laws grant the very right.